Pemanfaatan Media Interaktif untuk Meningkatkan Minat dan Kemampuan Bahasa Inggris Siswa di SD Negeri 047164 Seberaya - Kresna Ningsih Manik; Kesya Klarissya Br Pandia; Helena Yusen (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This community service focuses on the utilization of interactive media to enhance the interest and English proficiency of students at SD Negeri 047164 Seberaya. It addresses the difficulties faced by elementary students in learning English due to conventional teaching methods and the lack of interactive media. Tools such as educational applications, animated videos, and digital games were applied to support multisensory and student-centered learning. Interactive media were implemented to improve learning interest, vocabulary skills, and speaking abilities of grades 1–3 students (30 students). The targets included 80% active participation, a 70% increase in interest, and improvement in basic English skills. The program was conducted over eight weeks, including preparation (coordination, equipment setup), implementation (warm-up, main activities using media, closing), and evaluation (observation, oral tests). The approach emphasized student-centered and multisensory learning. Learning interest increased by 30–35%, vocabulary skills from 40% to 78%, pronunciation from 35% to 72%, and simple sentence construction from 30% to 70%. Active participation reached 85–90%, accompanied by ongoing guidance for the school. Interactive media proved effective in significantly increasing students’ interest and English proficiency, consistent with the theories of Hidi & Renninger (2006) and Harmer (2007). It is recommended that such media be routinely implemented with adequate supporting facilities.